2022
DOI: 10.5365/wpsar.2022.13.4.987
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological overview of human infections with HxNy avian influenza in the Western Pacific Region, 2003–2022

Abstract: Avian influenza subtype A(HxNy) viruses are zoonotic and may occasionally infect humans through direct or indirect contact, resulting in mild to severe illness and death. Member States in the Western Pacific Region (WPR) communicate and notify the World Health Organization of any human cases of A(HxNy) through the International Health Regulations (IHR 2005) mechanism. This report includes all notifications in the WPR with illness onset dates from 1 November 2003 to 31 July 2022. During this period, there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Our report meticulously describes the rst case of human-infected avian in uenza H10N3 virus since the end of the COVID-19 pandemic. Similar to the onset of the rst two globally reported cases [5,8], human infection with the H10N3 virus initially presents with common symptoms of respiratory disease, such as fever, cough, shortness of breath, and fatigue. These symptoms could be easily overlooked, leading to delayed treatment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our report meticulously describes the rst case of human-infected avian in uenza H10N3 virus since the end of the COVID-19 pandemic. Similar to the onset of the rst two globally reported cases [5,8], human infection with the H10N3 virus initially presents with common symptoms of respiratory disease, such as fever, cough, shortness of breath, and fatigue. These symptoms could be easily overlooked, leading to delayed treatment.…”
Section: Discussionmentioning
confidence: 77%
“…[H10N7]) [1].The rst human case of avian in uenza H10N3 was reported in Jiangsu Province, China in April 2021 [2,3].As of the latest WHO weekly report on avian in uenza surveillance until March 8th 2024, only two human cases of avian in uenza sub-type H10N3 have been reported globally, both in China [4]. This has become a public health concern worldwide [5][6][7]. In March 2024, a third case of avian in uenza H10N3 was reported in Kunming, Yunnan Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have identified about 1687 human cases associated with the H7 influenza strain across eight countries until 2019, while the H7N9 strain has infected ~1568 people, claiming the lives of 616 individuals. Recently, new sub-types, including H3N8, H7N4, and H10N3, have been identified to cause human infections in China [4] . Additionally, the H3Ny subtypes of AIV have been found to possess the broadest host range, encompassing humans, pigs, wild birds, poultry, dogs, horses, cats, and seals, thereby presenting a highly alarming potential for widespread epidemic outbreaks [2] .…”
mentioning
confidence: 99%